On the Occurrence of Eriolaena stocksii Hk.f. & TH. From Gujarat - Shah, G. L.; Suryanarayana, B. (Indian Forester, 1968)
In this paper the fruits of Eriolaena stocksii Hk. F. & Th. Are reported for the first time on the strength of collections made from Dangs forest, Gujarat, included within the limits of erstwhile Bombay Presidency. E. stocksii Hk. F. & Th. And E. hookeriana W. & A. are considered distinct. Illustrations of the two plants are given for a comparative study.